2015
DOI: 10.1177/0963721415573203
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-Induced Forgetting and Context

Abstract: Retrieving information can result in the forgetting of related information, a phenomenon referred to as retrieval-induced forgetting (RIF). To date, the dominant explanation of RIF has been an inhibition account, which emphasizes longterm suppression of interfering memories. As one alternative, some have advocated for a strength-based interference account, which emphasizes the role of strengthening associations. More recently, we have proposed a context account, which emphasizes the role of context change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Although we observed evidence for RIFA, studies of retrievalinduced forgetting (RIF) (2,(32)(33)(34)(35) typically show that retrieval can impair recall of related, nonretrieved information. Chan (8) has determined that at least two factors affect whether retrieval will facilitate or impair memory for linked items.…”
Section: Discussioncontrasting
confidence: 65%
“…Although we observed evidence for RIFA, studies of retrievalinduced forgetting (RIF) (2,(32)(33)(34)(35) typically show that retrieval can impair recall of related, nonretrieved information. Chan (8) has determined that at least two factors affect whether retrieval will facilitate or impair memory for linked items.…”
Section: Discussioncontrasting
confidence: 65%
“…These demonstrations of reduced repetition priming have theoretical implications for the mechanisms underlying suppression-induced forgetting. For instance, putatively inhibitory effects observed on episodic cued-recall tests may instead reflect non-inhibitory mechanisms such as associative interference (e.g., Hertel & Calcaterra, 2005 ) or changes in context ( Jonker, Seli, & MacLeod, 2015 ). Through these mechanisms, during the no-think task, the reminder cues become associated with alternative, distracting thoughts (associative interference) or with a new experimental context (context change); later, during the final cued-recall test, the reminder cues may now elicit either the alternative associations participants had formed (interference view) or the novel TNT-phase context associated with the reminder (context-change view), impairing memory for the original item, which is encountered only in the original study context.…”
Section: Suppression Reduces the Unintended Influence Of Memory On Bementioning
confidence: 99%
“…Regarding the results of the RIF test, to provide an appropriate baseline for the RP− and RP+ items that occurred in different testing positions, we divided the NRP items in each category in half based on their testing positions. RP− items were compared to the first three NRP items tested (NRP1), whereas RP+ items were compared to the last three NRP items tested (NRP2; Jonker & MacLeod, 2012;Jonker, Seli, & MacLeod, 2015). Results of a repeated-measure analysis of variance revealed that recall for RP−, RP+, NRP1, and NRP2 items differed significantly, F(3, 87) = 27.3, p < 0.001.…”
Section: Resultsmentioning
confidence: 98%